Differential Reporting: What Does it Really Mean for the Public Sector? - Pilcher, Robyn; Gilchrist, D. (Routledge, 2018)
The history of accounting can be traced back hundreds of years with double entry accounting first transcribed by Cotrugli and Pacioli in 1458 and 1494 respectively (Yamey 1994). Since then financial reporting, including Generally Accepted Accounting Principles (GAAP), has developed through the centuries. One of the major turning points in the United States (US) was the Great Depression which triggered comprehensive reform beginning in 1930 with the American Institute of Accountants and the New York Stock Exchange reviewing financial reporting requirements (Financial Accounting Foundation n.d.). According to the Financial Accounting Foundation (n.d.), their main aim was the provision of information to aid in decision-making by users. Other countries followed suit, including Australia, always with this same key message as the objective. It is how that information is transmitted that continues to result in much debate amongst accounting standard setting bodies. Differential reporting became topical when the International Accounting Standards Board (IASB) introduced International Financial Reporting Standards (IFRS) for Small and Medium-sized Entities (SMEs) in July 2009. This chapter fills a gap in the current literature by, initially, considering the impact on the public sector in general if a differential reporting system is introduced. Then, it examines more closely the Australian Reduced Disclosure Requirements (RDR) regime—something other countries could consider instead of IFRS for SMEs. Taken in the context of value as defined in this chapter, findings reveal that not all criteria in terms of efficiencies, clarity and transparency, are met. For the public sector there are bigger issues at stake in terms of accountability that neither the IFRS nor RDR have addressed.